مكافحة الإرهاب في إطار قانون المملكة العربية السعودية والقانون الدولي : دراسة مقارنة - بقمي، زابن بن عمر بن زابن (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2019)
The research aims at identifying the difference between the Saudi law and the international laws in combating terrorism and to determine its effectiveness and capabilities of each law to minimizing the crime. The researcher highlights the Kingdom of Saudi Arabia's policies in dealing with terrorist crimes and preventing them. In order for the researcher to do this, he follows the method of induction and description in engaging the opinions of experts on the field in discussing terrorism issues. The researcher also looks at the method of analysis in describing the laws and legal provisions used in the Kingdom that deals with issues of terrorism as well as international laws. In addition, the researcher uses the comparative approach in highlighting the difference between the Saudi government and the International treaties and laws for combating terrorism and explaining the different approaches used by Saudi Arabia as an Islamic country. The study concludes that there is a clear difference between the Saudi government in the fight against terrorism and international laws, especially in terms of imposing harsh sanctions and strict measures on the perpetrators of the crime of terrorism. The study recommends cooperation and joint actions between countries and international organizations such as the United Nations in combating all terrorism issues and means of financing it. At the same time to provide legal mechanism in combating this crime.